Credit constraints and aquaculture productivity. Issue 4 (2nd October 2019) - Mitra, Sandip; Khan, Md. Akhtaruzzaman; Nielsen, Rasmus
Abstract: The aquaculture sector is a capital intensive production process where access to credit is helpful in order to develop and manage farms in developing countries. Nevertheless, a supply of credit is often not readily available, which is creating credit constraint situations. This study investigates how credit constraints affect the productivity of aquaculture farmers in Bangladesh. An endogenous switching regression model is used to estimate the effects of credit constraints on productivity. The results show that productivity is significantly higher for farmers who are not exposed to credit constraints. This result reveals significant production-enhancing effects when using modern inputs for both constrained and unconstrained farmers. However, the effects are larger for the credit-unconstrained farmers because they have the opportunity to buy higher quality inputs and use them in a better input mix.